Locating Cities and Their Governments in Multi-Level Sustainability Governance - Hickmann, Thomas (2021)
Cities and their governments are increasingly recognized as important actors in global sustainability governance. With the adoption of the 2030 Agenda for Sustainable Development, their role in the global endeavor to foster sustainability has once again been put in the spotlight. Several scholars have highlighted pioneering local strategies and policies to implement the Sustainable Development Goals and render urban areas more sustainable. However, the question of how such urban sustainability actions are embedded in complex interactions between public and private actors operating at different levels has not been studied in enough detail. Building upon a multi-level governance approach, this article explores the entanglement and interconnectedness of cities and local governments with actors and institutions at various levels and scales to better capture the potential and limitations of urban policymaking contributing to global sustainability. The article finds that on the one hand cities and their governments are well positioned to engage other actors into a policy dialogue. On the other hand, local authorities face considerable budgetary and institutional capacity constraints, and they heavily rely on support from actors at other governmental levels and societal scales to carry out effective sustainability actions in urban areas.